PENGARUH PENGETAHUAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN TAMBAK UDANG DI DESA AKAR-AKAR LOMBOK UTARA - Febrianti, Ni Made Ari; Animah, Animah; Mariadi, Yusli (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p17, 2023)
This research was an effect of knowledge and motivation on the employment of shrimp pond workers in Akar-akar village Lombok Utara using a reported closed Likert scale questionnaire. This researc involves a collaborative study using quantitative methods. All populations in this study belong to them employees working in shrimp ponds with roots I and roots II during the period 2020 to 2021. The sampling method used in the non-probability sampling method taken, namely fill sample (registration) 80 shrimp pond employees were obtained. it was used as a research model. Data were analyzed using path analysis techniques (Path Analysisi). The results of the first assumption  indicate that knowledge has a positive impact on employee performance and the results of the second hypothesis indicate that motivation has a positive effect on the performance of shrimp pond employees.